Hubungan Antara Self Esteem Dengan Resiliensi Akademik Mahasiswa Fkip Universitas Tadulako - Bahrul Ulum; Nurwahyuni Nurwahyuni; Dhevy Puswiartika; Dian Fitriani (Universitas Batanghari Jambi, 2026)
New students often face complex academic and social adaptation challenges, which require academic resilience to survive and succeed. This study aims to determine the relationship between self-esteem and academic resilience in new students at the Faculty of Teacher Training and Education, Tadulako University. Data collection was conducted using a Likert scale for self-esteem and an academic resilience scale on 338 new students at the Faculty of Teacher Training and Education, Tadulako University, as a sample, which was then analyzed using Spearman's bivariate correlation test with the assistance of SPSS version 27. The results of the study show that the null hypothesis (Ho) is rejected, which means that there is a significant positive relationship between self-esteem and academic resilience in new students. These findings indicate that the higher the self-esteem of students, the higher their academic resilience in facing challenges in college. These results are expected to be the basis for the development of intervention programs to improve the adaptability of new students in a college environment